EVALUASI PELAKSANAAN PROGRAM PENGEMBANGAN KAWASAN MINAPOLITAN DENGAN MODEL CIPP (CONTEX, INPUT, PROCESS, PRODUCT) DI KOTA BITUNG - Silke . Pantouw; Charles R. Ngangi; Tommy F. Lolowang (AGRI-SOSIOEKONOMI, 2017)
This study aims to evaluate the Implementation of Minapolitan Area Development Program with CIPP Model (Context, Input, Process, Product in Bitung City) This research was conducted from May until July 2016 in Bitung City The data collection method used is primary and secondary data. The analytical method used in this research is descriptive qualitative analysis which is used to clearly describe the condition of development of Minapolitan area in Bitung City Evaluation model used is CIPP Evaluation Model (Context, Input, Process, Product, Result) The result of the research is Context Evaluation (1) Based on the evaluation of the implementation context of the development program of Minapolitan area in Bitung City is very suitable if the City of Bitung stipulated by the decree of the minister of marine and fishery Number KEP.32 / MEN / 2010 because Bitung City meets the requirements of a region determined as gai area minapolitan one of which is a strategic location and natural resources available. (2) Based on input evaluais seen from several aspects, among others: (a) infrastructure aspect, (b) institutional aspect and regulation, (c) funding aspect, (3) Based on process evaluation, where the blue ocean port becomes the motto of the mover and the harbor continues to be developed to match the fishing port in the Philippines. (4) Based on product evaluation, the implementation of minapolitan program in Bitung City increases the volume and value of capture fisheries production in Bitung City.